Beyond Fmoc: a review of aromatic peptide capping groups - Martin, Adam D; Thordarson, Pall (Journal of materials chemistry. B, Materials for biology and medicine, 2020)
Self-assembling short peptides have attracted widespread interest due to their tuneable, biocompatible nature and have potential applications in energy materials, tissue engineering, sensing and drug delivery. The hierarchical self-assembly of these peptides is highly dependent on the selection of not only amino acid sequence, but also the capping group which is often employed at the N-terminus of the peptide to drive self-assembly. Although the Fmoc (9H-fluorenylmethyloxycarbonyl) group is commonly used due to its utility in solid phase peptide synthesis, many other aromatic capping groups have been reported which yield functional, responsive materials. This review explores recent developments in the utilisation of functional, aromatic capping groups beyond the Fmoc group for the creation of redox-responsive, fluorescent and drug delivering hydrogel scaffolds.